Containing climate change: The new governmental strategies of catastrophic environments. (September 2021) - Beuret, Nicholas
The only existing plans to arrest dangerous climate change depend on either yet to be invented technologies to keep us below 2°C or on crashing the world economy for decades to come. The political choice appears to be between doing what is scientifically necessary or what is politically realistic; between shifting to an entirely different kind of global socio-economic system or suffering catastrophe. We are thus in a moment of governmental impasse, caught between old and still-emerging political rationalities. Working through the liminal governmental role of environmental non-governmental organisations, this paper explores the shift from governmental regimes centred on biopower to ones that work through the register of geopower, from governing life to governing the conditions of life. Confronted with climate change as an irresolvable problem, what we find emerging are techniques that aim to contain the worst effects of climate change without fundamentally transforming the global economy.